Dopaminergic Modulation of Risky Decision-Making - Simon, Nicholas W. (Society for Neuroscience, 2011)
Many psychiatric disorders are characterized by abnormal risky decision-making and dysregulated dopamine receptor expression. The current study was designed to determine how different dopamine receptor subtypes modulate risk-taking in young adult rats, using a “Risky Decision-making Task” that involves choices between small “safe” rewards and large “risky” rewards accompanied by adverse consequences. Rats showed considerable, stable individual differences in risk preference in the task, which were not related to multiple measures of reward motivation, anxiety, or pain sensitivity. Systemic activation of D2-like receptors robustly attenuated risk-taking, whereas drugs acting on D1-like receptors had no effect. Systemic amphetamine also reduced risk-taking, an effect which was attenuated by D2-like (but not D1-like) receptor blockade. Dopamine receptor mRNA expression was evaluated in a separate cohort of drug-naive rats characterized in the task. D1 mRNA expression in both nucleus accumbens shell and insular cortex was positively associated with risk-taking, while D2 mRNA expression in orbitofrontal and medial prefrontal cortex predicted risk preference in opposing nonlinear patterns. Additionally, lower levels of D2 mRNA in dorsal striatum were associated with greater risk-taking. These data strongly implicate dopamine signaling in prefrontal cortical-striatal circuitry in modulating decision-making processes involving integration of reward information with risks of adverse consequences.